The unity of knowledge and etiquettes in Ihya' Ulum al-Din : with special reference to kitab al-Ilm - Norliza binti Ab Halim (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2012)
Al-Ghazali's ideas in the IÍya' 'Ulum al-Din influenced many prominent Muslim thinkers especially in sufism and Islamic philosophy. His works have become references to various Islamic as well as non-Islamic scholars and institutions. Therefore, this study is going to explicate his ideas on knowledge and etiquettes; and thus identify the importance of the unity in shaping one's attitude. The purpose of this study is to see the importance of knowledge and etiquettes as a basis of shaping one's attitude thus attaining happiness as a goal of living this life for the sake of the hereafter based on al-Ghazali's IÍya´ 'Ulum al-Din. The methodology of this research would mainly center on textual analysis. The discussion pertaining knowledge and etiquettes are wide and al-Ghazali considered these two integral parts as a requirement to be successful in this world as well as in the hereafter. Despite his many other works, the researcher found that it is sufficient to explore his ideas in the book of knowledge (Kitab al-ÑIlm) only and it is justified and contemporarily relevant to the issues faced by many Muslims nowadays.